Investigating the effectiveness of workshops in improving MUET achievement - Kamarudin, Rafidah; Zainal Abidin, Dzeelfa; Zainal Arifin, Mazliyana; Mohd Ali, Siti Nur Dina; Almuddin, Syahirah; Ong, Woon Chuan (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
The Malaysian University English Test (MUET) is a mandatory English proficiency exam for entry into Malaysian public universities, assessing students’ speaking, reading, writing, and listening skills and awarding bands from 1 to 6. Many students struggle to achieve high bands due to challenges such as insufficient preparation, limited vocabulary and grammar knowledge, and time constraints. To address these issues, a team from the Academy of Language Studies (APB) at UiTM Negeri Sembilan conducted a workshop designed to improve students’ MUET performance by offering a comprehensive overview of the test along with strategies for all four components, delivered across two sessions: Listening & Speaking and Reading & Writing.